2007
DOI: 10.1890/06-0613
|View full text |Cite
|
Sign up to set email alerts
|

Slope Aspect Modifies Community Responses to Clear-Cutting in Boreal Forests

Abstract: Slope aspect modifies community responses to clear-cutting in boreal forests. Abstract. Slope aspect modifies microclimate and influences ecological processes and spatial distribution of species across forest landscapes, but the impact of slope aspect on community responses to disturbance is poorly understood. Such insight is necessary to understand landscape community dynamics and resilience. We compared bryophyte (liverworts and mosses) communities in matched 0.02-ha plots of four boreal stand types in centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 40 publications
(42 reference statements)
1
31
1
Order By: Relevance
“…For example, the forb E. angustifolium increased in cover, and C. agrestis decreased in cover. This finding was consistent with our personal observations and similar to previous findings on the vascular plant community in the boreal forest (Astrom et al 2007), deciduous forest (Fenton et al 2003), and stream-side forest . The four species groups of bryophytes all experienced substantial reductions in cover (Table 1), which further supported the previous observations of the bryophyte assemblage in the boreal forest (Astrom et al 2007), indicating that all existing bryophyte growth forms had high and immediate sensitivity to clear-cut logging.…”
Section: Short-term Responsessupporting
confidence: 94%
“…For example, the forb E. angustifolium increased in cover, and C. agrestis decreased in cover. This finding was consistent with our personal observations and similar to previous findings on the vascular plant community in the boreal forest (Astrom et al 2007), deciduous forest (Fenton et al 2003), and stream-side forest . The four species groups of bryophytes all experienced substantial reductions in cover (Table 1), which further supported the previous observations of the bryophyte assemblage in the boreal forest (Astrom et al 2007), indicating that all existing bryophyte growth forms had high and immediate sensitivity to clear-cut logging.…”
Section: Short-term Responsessupporting
confidence: 94%
“…This is contradictory to certain guidelines that promote wider strips at moist sites. Aspect is also important, since Northfacing edges suffer less from edge effects than south-facing (Hylander 2005;Å ström et al 2007). The location of the buffer in the landscape in relation to prevailing winds should be considered in making decisions on the width, especially in the case when only on side of a stream is cut and the other side of the stream is left untouched.…”
Section: Riparian Forest Speciesmentioning
confidence: 99%
“…Therefore, equator-ward slopes are often both warmer and drier and have larger temperature fluctuations than pole-ward slopes [22][24]. As a consequence, north- and south-facing slopes are potentially good candidates for studies on microclimatic gradients and have also shown to influence species composition [25]. However, the interactions of many climate-forcing factors (e.g.…”
Section: Introductionmentioning
confidence: 99%